Penerapan Media Quizizz dalam Meningkatkan Pemahaman Tajwid Siswa Kelas VII di SMPIT Daarul Hikmah Boarding School Bontang - Hidayati, Siti; Ikrar, Ikrar; Syamsiar, Syamsiar (Sekolah Tinggi Ilmu Tarbiyah Syamsul Ma'arif Bontang, 2025)
This study discusses the implementation of Quizizz as a learning medium to improve tajwid comprehension among Grade VII students at SMPIT Daarul Hikmah Boarding School Bontang. The research refers to a series of systematically designed learning processes utilizing interactive digital media, namely Quizizz, as a tool in tajwid instruction. Quizizz is a game-based learning platform that allows educational content to be delivered through engaging and interactive quizzes. This study employed a descriptive qualitative approach, with data collected through observation, interviews, and documentation in the form of pre-test scores, post-test scores, and oral tajwid assessment results. Data analysis was conducted through the stages of data reduction, data display, and conclusion drawing. The findings reveal that the use of Quizizz has a positive impact on students’ understanding of tajwid. Teachers utilized interactive features such as automatic scoring, leaderboards, and paper mode during apperception, practice, and evaluation activities. The learning process became more enjoyable, interactive, and competitive, encouraging students to be more active, confident, and focused. An improvement in understanding was evident from the increase in the average pre-test score of 72.21 to a post-test score of 86.16. Oral assessment results also showed that all students improved, with most falling into the “good” category and one student achieving the “very good” category. These findings indicate that Quizizz is effective as a tajwid learning medium that supports students’ comprehensive understanding.